Evaluation of changes in antimicrobial susceptibility in bacteria infecting children and their mothers in pediatric, neonatal-intensive care unit, and gynecology/obstetrics wards of a quaternary referral hospital during the COVID-19 pandemic - Pinheiro, Felipe Ramos; Rozza-de-Menezes, Rafaela Elvira; Blum, Marina Camille; Pereira, Renata Freire Alves; Rocha, Jaqueline Abel; Guedes Pinto, Maria Cristina F.; Penna, Bruno A.; Riley, Lee W.; Aguiar-Alves, Fabio (Frontiers in Microbiology, 2023)
The World Health Organization released a statement warning of increased risk for the incidence of multi-drug resistant microorganisms and the absence of new drugs to control such infections soon. Since the beginning of the COVID-19 pandemic, the prescription of antimicrobial agents has increased and may have accelerated the emergence of multi-drug resistant (MDR) bacteria. This study aimed to evaluate maternal and pediatric infections within a hospital from January 2019 to December 2021. An observational retrospective cohort study was performed at a quaternary referral hospital in a metropolitan area of Niteroi city, Rio de Janeiro state, Brazil. A total of 196 patients’ medical records were analyzed. The data from 90 (45.9%) patients were collected before the SARS-CoV-2 pandemic, 29 (14.8%) from the 2020 pandemic period, and 77 (39.3%) from the 2021 pandemic period. A total of 256 microorganisms were identified during this period. Out of those, 101 (39.5%) were isolated in 2019, 51 (19.9%) in 2020, and 104 (40.6%) in 2021. Antimicrobial susceptibility tests were performed on 196 (76.6%) clinical isolates. The exact binomial test showed that the distribution of Gram-negative bacteria was predominant. The most common microorganism was Escherichia coli (23%; n=45), followed by Staphylococcus aureus (17.9%, n=35), Klebsiella pneumoniae (12.8%, n=25), Enterococcus faecalis (7.7%, n=15), Staphylococcus epidermidis (6.6%, n=13) and Pseudomonas aeruginosa (5.6%, n=11). Staphylococcus aureus was the predominant species among resistant bacteria. Among the antimicrobial agents tested, the following were resistant, presented on a descending scale: penicillin (72.7%, p=0.001, Binomial test), oxacillin (68.3%, p=0.006, Binomial test), ampicillin (64.3%, p=0.003, Binomial test), and ampicillin/sulbactam (54.9%, p=0.57, Binomial test). Infections with S. aureus were 3.1 times greater in pediatrics and maternal units than in other hospital wards. Despite the global reduction in the incidence of MRSA, we observed an increase in MDR S. aureus in this study. No changes were observed in the frequency of resistance profiles of the clinical isolates after the establishment of the global SARS-CoV-2 pandemic. More comprehensive studies are needed to understand the impact of the global SARS-CoV-2 pandemic on the resistance levels of bacteria associated with neonate and pediatric patients.